Population- and Gender-Based Investigation for Prevalence of Helicobacter pylori in Dhamar, Yemen - Dhary A. Almashhadany; Sara M. Mayas; Hero I. Mohammed; Abdulwahed A. Hassan; Izhar U. H. Khan (Canadian Journal of Gastroenterology and Hepatology)
Among 35 species of genus Helicobacter, H. pylori is the most common causative agent of human gastritis, peptic ulcer, and gastric cancer. The infection can spread through direct human-to-human contact, fecal–oral route, and contaminated water. The study was designed to investigate the rate of prevalence of H. pylori in the population of Dhamar, Yemen. In this one-year study, 460 including 250 male and 210 female stool specimens were collected between January to December 2020 in Dhamar Governorate, Yemen. Of the total 460, 215 rural (male: n = 120 and female: n = 95) and 245 urban (male: n = 130 and female: n = 115) specimens were investigated for identification of H. pylori by serological test using Helicobacter pylori stool antigen (HpSA) test. In addition, for comparing an improved recovery of H. pylori, conventional culture-based isolation was also carried out using three selective media. Modified Campy-blood Agar (MCA), Belo Horizonte Agar (BHA), and Egg yolk Emulsion (EYE) medium supplemented with antimicrobial agents including vancomycin (10 mg/L), cefsulodin (5 mg/L), trimethoprim (5 mg/L), and amphotericin B (5 mg/L) and isolates were phenotypically characterized. The HpSA test results revealed that of the total 460 specimens, 89 (19.3%) were positive for H. pylori with relatively low in male (n = 43; 17.2%) as compared to the female (n = 46; 21.9%) specimens. After 3–10 days of incubation, H. pylori was recovered at a variable rate on each selective (MCA: 16.5%; BHA: 15.0%; EYE: 13.0%) media. However, culture-based assay results showed less recovery (n = 81; 17.6%) with no significant difference among all selective media tested and between genders (male: n = 39; 15.6%; female: n = 42; 20.0%). The infection rate was comparatively higher in rural (n = 45; 20.9%) as compared to urban (n = 36; 14.7%) population. Overall, the study data showed the prevalence of infection in both genders of all age groups. The present study showed a relatively high rate of infection of H. pylori in the Dhamar population. The serological identification and culture-based methods are important for rapid detection, aid in treatment, and developing policies for the control and eradication of H. pylori infection and to prevent the disease in different age groups in Yemen.